UHPLC-LTQ-Orbitrap MS combined with spike-in method for plasma metabonomics analysis of acute myocardial ischemia rats and pretreatment effect of Danqi Tongmai tablet. Issue 2 (24th November 2014) - Yan, Bingpeng; Deng, Yanping; Hou, Jinjun; Bi, Qirui; Yang, Min; Jiang, Baohong; Liu, Xuan; Wu, Wanying; Guo, Dean
Abstract : Metabonomics analysis revealed the presumable pathological processes in the early stages of AMI and provided useful information on the pretreatment efficacy of DQTM. Abstract : Undoubtedly, metabonomics can reveal the comprehensive efficacies of traditional Chinese medicine (TCM) formulae and its complex mechanism at the molecular biological level. In this study, an attempt was made to address the pretreatment effect of a TCM formula. In this case, as a critical point, we should first know how to really reflect the various endogenous metabolites in a disease status before a TCM formula is employed in a therapeutic procedure. Here, we explored an approach that combined high resolution LTQ-Orbitrap mass spectrometry with a spike-in method to characterize endogenous metabolites in acute myocardial ischemia (AMI) rats. As a result, 19 potential biomarkers in rat plasma were identified and 10 related disturbed pathways were perturbed in the early stages of AMI development. Subsequently, the metabonomics method was applied to investigate the pretreatment effect of the TCM formula named the Danqi Tongmai tablet (DQTM). The results revealed that the DQTM pretreatment could reduce the AMI injury and partially regulate the perturbed TCA cycle and amino and nucleotide metabolism, which were presumable related to energy metabolism and myocardial cells apoptosis/necrosis. In conclusion, UHPLC-LTQ-Orbitrap MS combined with a spike-in method were successfully applied to the metabonomics analysis of DQTM, which demonstrated that not only a comprehensive metabolic profile in the early stages of AMI development was achieved, but also that the underlying holistic efficacies were assessed and it was helpful to understand the possible mechanism of pretreatment with DQTM.